Clocked single-spin source based on a spin-split superconductor - Niklas Dittmann; Janine Splettstoesser; Francesco Giazotto (New Journal of Physics, 2016)
We propose an accurate clocked single-spin source for ac-spintronic applications. Our device consists of a superconducting island covered by a ferromagnetic insulator (FI) layer through which it is coupled to superconducting leads. Single-particle transfer relies on the energy gaps and the island's charging energy, and is enabled by a bias and a time-periodic gate voltage. Accurate spin transfer is achieved by the FI layer which polarizes the island, provides spin-selective tunneling barriers and improves the precision by suppressing Andreev reflection. We analyze realistic material combinations and experimental requirements which allow for a clocked spin current in the MHz regime.